Mediação como base de estratégias pedagógicas voltadas a alunos com deficiência mental severa: indicadores para a prática docente - Caramori, Patrícia Moralis [UNESP]; Heredero, Eládio Sebástian; Dall'Acqua, Maria Júlia Canazza [UNESP] (My University, 2011)
The paper talks about the education of persons with disabilities severe mental retardation based on the idea of Reuven Feuerstein mediation. The collected data were analysed mainly under the focus quantitative, allowing extraction of details of everyday life investigated. Aims to describe and analyze the implementation process their educational, focusing on teaching strategies used by Special Education teachers in the Araraquara’s city. In addition, seeks to address the educational process of a population slightly investigated by uniting two strands of thread in an innovative way: the Theory of Structural Cognitive Modifiability (SCM) and Reuven Feuerstein education of students with severe cognitive impairment. The methodology initiated by the establishment of the teacher’s profile, their mapping and location. Data collection was achieved through three instruments: interviews with teachers, observation protocol and field diary for registration. Our results describe the work of a teacher, showing their practice, and enlist the pedagogical strategies used, mainly those related to the criteria medication. According to the Theory of Structural Cognitive Modifiability (SCM) and the idea of Mediated Learning Experience (MLE), the teacher acts as mediator, interposing themselves between stimuli the environment and the student. The work of the teacher observed indicates that the environment and the student. The work of the teacher observed indicates that she exerts her functions in teaching using pedagogical strategies which are found in her heart, precepts essential to mediation. This shows it is possible to associate the ideas of Feuerstein practices aimed at teaching students with severe mental disabilities.

A pesquisa aborda a temática da educação de pessoas com deficiência mental severa com base na idéia de mediação de Reuven Feuerstein. Os dados coletados foram analisados majoritariamente sob o enfoque qualitativo, permitindo a extração de detalhes do cotidiano investigado. Tem por objetivo descrever e analisar a implementação do processo educacional desses alunos, enfocando as estratégias pedagógicas utilizadas por professoras de Educação Especial na cidade de Araraquara. Além disso, busca tratar o processo educacional de uma população pouco investigada unindo dois eixos de discussão de forma inovadora: a Teoria da Modificabilidade Cognitiva Estrutural (MCE) de Reuven Feuerstein e a educação de alunos com comprometimento cognitivo severo. A metodologia iniciou-se pelo estabelecimento do perfil do professor, seu mapeamento e localização. A coleta de dados se deu por meio de três instrumentos: entrevista com as professoras, protocolo de observação e diário de campo para registro. Os resultados descrevem o trabalho de uma professora, evidenciando sua prática, além de arrolar as estratégias pedagógicas utilizadas, principalmente, as relacionadas com os critérios de medicação. De acordo com a MCE e a idéia de Experiência de Aprendizagem Mediada, o professor atua como mediador, interpondose entre os estímulos do ambiente e o aluno. O trabalho da professora observada mostra que a mesma exerce sua função docente empregando estratégias pedagógicas nas quais são encontrados, em seu cerne, preceitos essenciais à mediação. Isso mostra ser possível associar as idéias de Feuerstein às práticas pedagógicas voltadas a alunos com deficiência mental severa.
Mediation as the basis for teaching strategies geared to students with severe learning disabilities: indicators for teaching pratice
Keywords: Pedagogical strategies; Learning experience mediated; Pedagogical practices; Estratégias Pedagógicas; Experiência de Aprendizagem Mediada; práticas pedagógicas